Traditional use of the genus Lippia sp. and pesticidal potential: A review. (March 2022) - Camilo, Cicera Janaine; Duarte Leite, Débora Odília; de Fatima Alves Nonato, Carla; Gomes de Carvalho, Natália Kelly; Ribeiro, Daiany Alves; Martins da Costa, José Galberto
Abstract: The understanding of popular knowledge has guided the studies involving promising natural products for the development of botanical insecticides, through ethnobotanical research. The frequent records of scientific research with the genus Lippia demonstrate a high insecticidal potential for the species, with prospects of new products for the market. Therefore, it is important to recognize the contribution of traditional knowledge and use it in plant selection for in-depth research that can lead to the elaboration of a final product. Thus, the aim of this research was to analyze existing relationships between ethnobotanical studies and research related to the control of insects, mites and ticks with the genus Lippia sp., as well as to verify the difficulties and perspectives for the development of new products derived from species of this genus for the fight pests. The main indications in the ethnobiological survey were medicinal for diseases of the gastrointestinal tract (34.2%), respiratory system (27.1%) and nervous system (22.18%), in addition to these, six species had indications for use as repellent. For the pesticide survey, the essential oils of the species L. alba and L. sidoides were the most investigated, being thymol and carvacrol, the most frequently identified compounds. The species L . alba was the most cited in both surveys, demonstrating an influence between the indications of traditional uses and biological investigations for the genus. Graphical abstract: Image 1 Highlights: The genus Lippia has a high indication as a therapeutic. Essential oils are the most investigated as pesticides. L. alba is widely cited in ethnobotany and also as a pesticide.. Thymol and carvacrol are the majority in Lippia essential oils.